Decreased serum microRNA-21 level is associated with obesity in healthy and type 2 diabetic subjects. (8th August 2018) - Ghorbani, Samira; Mahdavi, Roya; Alipoor, Behnam; Panahi, Ghodratollah; Nasli Esfahani, Ensieh; Razi, Farideh; Taghikhani, Mohhammad; Meshkani, Reza
Abstract: Background: Recently, much attention has been paid to the role of circulating microRNAs (miRNAs) as novel biomarkers for various diseases. The aim of this study was to investigate the level of a subset of miRNAs in serum samples of the diabetic and healthy subjects. Methods: Forty two healthy and 45 T2D subjects participated in this study. Serum miR-21, miR-126, and miR-146a levels were measured using real-time PCR. Results: There was no significant difference in the serum level of miR-21, miR-126, and miR-146a between the diabetic and non-diabetic groups. The level of miR-21 in obese non-diabetic and diabetic subjects was significantly lower than lean subjects. Correlation analyses in non-diabetic and diabetic groups revealed a significant negative correlation between the amount of miR-21 and body mass index, waist circumference, insulin, and HOMA-IR levels. Conclusions: A reduced level of miR-21 might associate with obesity and its related metabolic traits such as hyperinsulinaemia.